A study of outcome of induction of labour with foley’s balloon in previous LSCS cases - Jois, Srinivas Krishna; M., Sunanda K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour in a scarred uterus is a controversial topic in Obstetric practice, but in carefully selected and monitored cases never the less the outcome is gratifying. When the baby is non-salvageable, or in cases of IUFD, it is always desirable to achieve a vaginal delivery. Many of the professional organizations recommend induction of labour in previous LSCS. Thus, this study was done to evaluate the success rate, determinants of failure and complications of induction of labour with foley’s catheter in patients with previous 1 LSCS. Methods: 62 patients were recruited over a period of 1 year and studied at Vani Vilas Hospital, Bangalore Medical College and Research Institute, all with previous 1 LSCS. 34% of them were with past h/o 1 or more vaginal delivery. 8% were term pregnancies, 64% were between 28-32 weeks. Induction was done for IUFD in 56% and, HDP warranting termination in 44%. Induction done with Foley’s catheter, expulsion of catheter with filled bulb and uterine contraction initiation was taken as successful induction. The patient profile in cases of failure was noted. Results: 83% was the success rate for induction out of which 30% cases required additional PGE2 gel. Oxytocin and ARM alone or together were used for augmentation in 90% cases. Induction to foley’s expulsion average duration was 14 hours. Post expulsion delivery happened at an average time interval of 5 hours. One patient had rupture uterus during the course of augmentation. Conclusions: Induction can be done safely in carefully selected cases of previous LSCS with Foley’s Balloon.